From Flor to Mary Jane divergences, intersection and trajectories - Olalia, Edre U. (Quezon City UP Diliman Gender office, 2017)
Although the cases of Flor Contemplacion and Mary Jane Veloso crept into the national consciousness under radically different circumstances, both of their narratives fundamentally show the culpability of a decrepit socio-economic system that has pushed millions of poor Filipinos to seek perceived better opportunities abroad. In turn, however, their struggles have ushered various insights into how similar cases can be more effectively handled by progressive people's organizations and lawyers' groups in the future with the view of ending the iniquitous labor-export policy of the government.
Paper delivered at the public fora "A tale of two women: a forum on poverty, migration and trafficking", organized by the UP Diliman Gender office on 26 November 2015, Benitez Theater, College of Education, UP Diliman, Quezon City, and "In the shadow of the gallows: from Flor to Mary Jane-In defense of our migrant workers" organized by the National Union of People's Lawyers on 22 May 2015, College of Mass Communication, UP Diliman, Quezon City, Philippines.
UCWS-3133g, UCWS-3134g, UCWS-3135g, UCWS-3136g donated by UP Diliman Gender office - June 2017.
Keywords: Foreign workers, Filipinos -- Legal status, laws, etc; Filipinos -- Employment -- Foreign countries; Household employees -- Legal status, laws, etc; Women household employees -- Singapore; Women household employees -- Indonesia; Household employees -- Singapore; Household employees -- Indonesia